2021
DOI: 10.1007/s11356-021-14652-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection for low-cadmium cultivars and cadmium subcellular distribution comparison between two selected cultivars of eggplant (Solanum melongena L.)

Abstract: Excessive accumulation of cadmium (Cd) in vegetables poses a serious threat to human health; therefore, it is urgent to screen and cultivate vegetable cultivars with low Cd accumulation in the edible parts. Eggplant has a high tendency for Cd accumulation, but research on its low Cd accumulation cultivars is still rare. In this study, to screen low-Cd cultivars, 30 eggplant cultivars were screened using soils containing 0.22 mg/kg, 2.9 mg/kg (low-Cd), and 4.7 mg/kg of Cd (high-Cd). MYCQ and ZGQ were con rmed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In Brassica chinensis L., approximately 14.1% of Cd was adsorbed by lignin in the high-Cd cultivar, while 14.5% of Cd was adsorbed by the lignin of the low-Cd cultivar ( Wang et al., 2020 ). The lignin synthesis-related genes ( CADs and PODs ), lignin content as well as FTIR analyses of lignin (peaks at 1238 and 1157 cm -1 ) in MYQZ were significantly higher ( p <0.05) than that of BXGZ in this study, which are consistent with our previous study ( Shen et al., 2021 ), revealing that the distribution of Cd in the root cell wall is significantly higher in MYQZ than in BXGZ. Collectively, differences in lignin should also be an important factor in determining the Cd accumulation characteristics of eggplant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In Brassica chinensis L., approximately 14.1% of Cd was adsorbed by lignin in the high-Cd cultivar, while 14.5% of Cd was adsorbed by the lignin of the low-Cd cultivar ( Wang et al., 2020 ). The lignin synthesis-related genes ( CADs and PODs ), lignin content as well as FTIR analyses of lignin (peaks at 1238 and 1157 cm -1 ) in MYQZ were significantly higher ( p <0.05) than that of BXGZ in this study, which are consistent with our previous study ( Shen et al., 2021 ), revealing that the distribution of Cd in the root cell wall is significantly higher in MYQZ than in BXGZ. Collectively, differences in lignin should also be an important factor in determining the Cd accumulation characteristics of eggplant.…”
Section: Discussionsupporting
confidence: 92%
“…Comparative studies of high- and low-Cd cultivars in potato and hot pepper revealed that high-Cd cultivar possessed longer root length, more root tips, larger root surface area and root volume, which should contribute to its higher Cd uptake and translocation ( Huang et al., 2015 ; Xin et al., 2017 ). Our previous study revealed that the Cd net uptake via root of BXGZ under low and high Cd treatment was were significantly higher than those of MYQZ ( Shen et al., 2021 ). In this study, with the significantly higher expression of root development genes ( ARF19 , GATA4 , 5 , 11 and PIN5 ), BXGZ showed a more developed root system of BXGZ under Cd treatment, indicting the root development of eggplant should be a key factor affecting the Cd net uptake via roots.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Purple sepal eggplant varieties have higher anthocyanin concentrations compared to other darker colored fruits and vegetables. In brilliant flowering plants, color changes in the floral organs are closely associated with anthocyanins natural pigments that are widely found in plants [45]. They not only confer plants' vivid colors to attract pollinators and seed dispersers, but also enhance plants' resistance to stress [45].…”
Section: Eggplant Metabolism Plays a Key Role In The Color Of Eggplan...mentioning
confidence: 99%
“…In brilliant flowering plants, color changes in the floral organs are closely associated with anthocyanins natural pigments that are widely found in plants [45]. They not only confer plants' vivid colors to attract pollinators and seed dispersers, but also enhance plants' resistance to stress [45]. Anthocyanin synthesis and transport are intricately regulated processes that engage a multitude of structural genes and transcription factors, along with regulatory mechanisms at various levels, including RNA processing and protein modification [46].…”
Section: Eggplant Metabolism Plays a Key Role In The Color Of Eggplan...mentioning
confidence: 99%